PEMANFAATAN ISU SOSIO-SAINTIFIK TRADISI MENGINANG SEBAGAI KONTEKS BELAJAR IPA SMP - Riva Ismawati (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2019)
This study aims to examine the socio-scientific issues of the betel chewing tradition so that it can be used as a context for learning science lessons in junior high school. The research conducted is qualitative research with a case study approach. The population was residents of Genito Village, Windusari Subdistrict, Magelang District who still carried out the tradition of betel chewing. The research sample was determined using cluster random sampling technique and selected 4 respondents. The instruments used in the study are interview guidelines and observation guidelines. The results showed that the betel chewers believed that betel chewing could strengthen the teeth. Unfortunately, betel chewers do not maintain oral hygiene so that the activities of the chewing can have a negative impact. The socio-scientific issue of the tradition of  betel chewing can be built as a context for junior high school science learning activities.